Types, rings, and games - Chen, Wei (2012)
Algebraic equations on complex numbers and functional equations on generating functions are often used to solve combinatorial problems. But the introduction of common arithmetic operators such as subtraction and division always causes panic in the world of objects which are generated from constants by applying products and coproducts. Over the years, researchers have been endeavouring to interpretate some absurd calculations on objects which lead to meaningful combinatorial results. This thesis investigates connections between algebraic equations on complex numbers and isomorphisms of recursively defined objects. We are attempting to work out conditions under which isomorphisms between recursively defined objects can be decided by equalities between polynomials on multi-variables with integers as coefficients.